The normal choroidal thickness in southern Thailand - Jirarattanasopa, Pichai; Panon, Nisa; Bhurayanontachai, Patama; Hiranyachattada, Siriphun (Clinical ophthalmology (Auckland, N.Z.), 2014)
To investigate the association between subfoveal choroidal thickness in healthy southern Thailand volunteers and age, axial length, and refractive error. This was a prospective cross-sectional case series. A total of 210 eyes of 105 healthy volunteers (86 women, age 23-83 years) in southern Thailand were examined with enhanced depth-imaging optical coherence tomography. Subjects with systemic diseases that may affect the choroidal vascular blood vessels, such as diabetes, impaired renal function, and hypertension, were excluded. Refractive error and axial length were measured by autorefractometry and an IOLMaster, respectively. Subfoveal choroidal thickness was measured from the outer border of the retinal pigment epithelium to the inner scleral border in the subfoveal area. The mean subfoveal choroidal thickness was 279.4±75.49 μm, and the mean age was 46.4±16.45 years. Subfoveal choroidal thickness was negatively correlated with age (r (2)=0.33, P<0.0001) and axial length (r (2)=0.02, P<0.02). Multivariable regression analysis showed subfoveal choroidal thickness was positively and negatively correlated with a spherical equivalent refractive error and axial length, respectively, when adjusted for age. Age is the most important factor in choroidal thickness rather than axial length and refractive error. Subfoval choroidal thickness was decreased 2.67 μm every year and 14.59 μm with 1 mm increase in axial length.